Discrimination of Women and People with Disabilities in Labor Relations: Unraveling Challenges and Pursuing Equity in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article critically examines the persistent issues of discrimination within Uzbekistan's labor relations, focusing on women and people with disabilities. Through a comprehensive analysis of the legal framework, societal norms, and empirical data, the study unveils the multifaceted dimensions of gender bias and ableism that hinder equitable participation in the workforce. It explores the intersectionality of gender and disability discrimination, emphasizing the compounded challenges faced by marginalized groups. Drawing on international obligations and comparative perspectives, the article proposes practical policy recommendations to dismantle discriminatory practices. By shedding light on the complexities of discrimination in labor relations, this study contributes to the ongoing dialogue on social justice and calls for concerted efforts to create an inclusive and equitable work environment in Uzbekistan.